Ставок больше нет: [роман] / Елена Караваешникова - Караваешникова Елена Юрьевна (Маросейка 12, 2000)
Экземпляры: ф.3 (2003) / Инвентарный номер: 47299 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 21 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44